Outcomes of An Early Intervention Programme on Children with Autism Spectrum Disorders (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Autism Spectrum Disorders (ASD) is becoming global problem as it is being diagnosed very frequently amongst the non communicable diseases. Lack of socialization, communication skill and behavioural abnormality are the main problem belongs to the disease. Cornerstone of the management is based on early intervention program directed to improve the communication and socialization skill. In Bangladesh different early intervention strategies are implicated adopting from evidence based practices in the developed countries. To determine the effect of early intervention program on the improvement of socialization and communication skills of children with ASD who attended an early intervention programme at the Institute of Autism and Child Development, Chattagram Maa Shishu -O-General Hospital.Methods: This is a quasi experimental study carried out at Institute of Autism and Child Development, Chattagram Maa Shishu-O-General Hospital from January 2015 to December 2015. Children with ASD (Autism Spectrum Disorder) aged 1-5 years enrolled as study subjects which is fifty in number. Screening of ASD was carried out by psychological tools like M—Chat (1-3yrs) & ASD assessment scale (> 3yrs). Diagnosis was confirmed by ADOS-G (Autism Diagnosis Observation Schedule- Generic). Internvention was provided on a 1:1 basis which was adopted from various evidence based practices including the ‘More Than Words’. Intervention were given for three subsequent session in one month interval. Level of communications were measured after intervention and compared with pre intevvention level.Results: Significant improvements has been observed in overall level of communication and activities of daily living which included eye contact, attention, joint attention, turn taking, toilet training.Conclusion: A well planned early intervention programme for children with ASD can speed up the social communication development in such a way that gives rise to a hope of mainstreaming these children in future.Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 9-13